MAPbBr3 First‐Order Distributed Feedback Laser with High Stability. Issue 1 (18th August 2022) - Chang, Cheng; Shi, Yangwei; Zou, Chen; Lin, Lih Y.
Abstract : A green‐emitting perovskite first‐order distributed feedback (DFB) laser based on the methylammonium lead bromide (MAPbBr3 ) with high stability is demonstrated for the first time. The laser achieves stable lasing at 550 nm with a full width at half maximum of 0.4 nm. Low lasing threshold of 60 μJ cm −2 under nanosecond pulsed excitation and 3.1 μJ cm −2 under femtosecond pulsed excitation is observed, showing a much lower lasing threshold compared with the second‐order DFB cavities, which are fabricated on the same substrate. By optimizing the antisolvent treatment and encapsulating with poly(methyl methacrylate), the laser lifetime, resistance to moisture, lasing threshold, and intensity are significantly improved. The lasers are fabricated with a complementary metal‐oxide‐semiconductor‐compatible process, thus offer promising potential for the integrated photonic devices. Abstract : Herein, a perovskite first‐order distributed feedback (DFB) laser is presented. The laser is fabricated with a silicon dioxide DFB cavity and solution‐processed MAPbBr3 . It has low lasing threshold under nanosecond pulsed excitation, which is lower than the second‐order DFB laser on the same substrate. With antisolvent treatment and poly(methyl methacrylate) encapsulation, the laser's performance is further improved.